PENGEMBANGAN MEDIA MYSTERY BOX UNTUK KEGIATAN BINA IMAN ANAK KATOLIK PADA MATERI KEPEDULIAN SOSIAL - Natalis Sukma Permana; Romaldis Andini Noverian Kristanti (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2026)
This study aims to develop a creative learning media in the form of a Mystery Box game for Catholic Religious Education for Children (BIAK) activities that focus on social awareness material. The background of this study begins with the phenomenon of low interest in children to actively participate in BIAK due to monotonous teaching methods. By combining elements of play and learning, the Mystery Box is expected to increase motivation, involvement, and understanding of social awareness values ​​for children aged 9-12 years. This study uses the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The feasibility test includes validation by field experts, media experts, limited trials, and field trials at St. Hilarius Klepu Parish. The results of the study indicate that the Mystery Box media is